Determining the current indications for endoscopic submucosal dissection in patients with Lauren mixed‐type early gastric cancer. Issue 4 (6th November 2019) - Choi, Jinju; Chung, Hyunsoo; Kim, Jung; Kim, Jue Lie; Kim, Sang Gyun; Jung, Hyun Chae
Abstract: Background and Aim: Recent study showed that early gastric cancer (EGC) with Lauren mixed‐type (MT) histology is associated with worse prognosis. We aimed to evaluate the clinicopathologic features and prognostic significance of Lauren MT‐EGCs that meets the criteria for endoscopic submucosal dissection (ESD). Methods: We reviewed 2665 patients with EGC who underwent surgery between 2010 and 2015. The clinicopathologic features and invasiveness including lymph node metastasis (LNM) and lymphovascular invasion (LVI) of MT‐EGC were compared with those of intestinal type and diffuse type by Lauren histology. Results: Among 2665 patients, EGCs in 241 (9%) patients were classified as MT. Tumor size was larger and depth of invasion was greater than other histology. Among patients with MT‐EGC, 16.6% (40/241) showed LNM and 22.8% (55/241) showed lymphatic invasion, which were significantly higher than that of patients with other Lauren types (8.2% and 15.3% in intestinal type and 9.1% and 8.7% in diffuse type, P  < 0.001). This finding remained significant even after adjusting for depth of invasion. However, when we analyzed the patient groups who met the absolute or expanded criteria of ESD, no significant difference was observed in the rates of LNM or LVI or cancer mortality by Lauren classification. Conclusion: Mixed‐type early gastric cancer (MT‐EGC) exhibited larger tumor size, greater depth of invasion, and higher risk of LNM and LVI. However, among the patients who met the absolute or expanded criteria of ESD, no significant difference was observed in LNM, LVI, and gastric cancer mortality risk.